1998
DOI: 10.1111/j.1349-7006.1998.tb00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Responses Other than the Formation of DNA‐adducts between the Livers of Carcinogen‐resistant Rats (DRH) and Carcinogen‐sensitive Rats (Donryu) to 3′‐Methyl‐4‐dimethylaminoazobenzene Administration

Abstract: Carcinogen‐resistant inbred DRH rats developed from the Donryu strain showed a remarkably low incidence of liver tumors when they were fed diets containing hepatocarcinogens such as 3′‐methyl‐4‐dimethylaminoazobenzene (3′‐Me‐DAB). In this work, we examined various characteristics of male DRH and Donryu rats during 3′‐Me‐DAB administration for 8 weeks. 32P‐Postlabeling analysis showed that essentially similar levels of DNA‐adducts were generated by the metabolites of 3′‐Me‐DAB in the livers of these two strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Because DAB metabolism through the mono-oxygenase system is responsible for liver damage, decrease in P450 could ameliorate or delay this process (Yan et al, 1998). However, the significant increase in GST activity provoked by DAB still persisted in animals also receiving CIM, indicating that reduction in P450 by CIM is not enough to completely overcome DAB toxicity and suggesting that other mechanisms would be participating in the whole process.…”
Section: Discussionmentioning
confidence: 99%
“…Because DAB metabolism through the mono-oxygenase system is responsible for liver damage, decrease in P450 could ameliorate or delay this process (Yan et al, 1998). However, the significant increase in GST activity provoked by DAB still persisted in animals also receiving CIM, indicating that reduction in P450 by CIM is not enough to completely overcome DAB toxicity and suggesting that other mechanisms would be participating in the whole process.…”
Section: Discussionmentioning
confidence: 99%
“…These results support our previous finding that DNA damage other than bulky DNA adduct formation is involved in the carcinogenic mechanism of 3′-MeDAB. 8) To obtain further information about the repair capacity, we analyzed the mRNA level of the repair enzyme OGG1 by RT-PCR. The OGG1 protein is an 8-OH-Gua repair enzyme, and has glycosylase/lyase activities.…”
Section: Discussionmentioning
confidence: 99%
“…8) We concluded that DNA damage other than bulky DNA adduct formation was involved in the mechanism of 3′-MeDAB-induced carcinogenesis. We also suggested that the generation of reactive oxygen species occurred as well, because we observed a significant induction of cytochrome P-450 2E1 mRNA (CYP2E1) in the Donryu rat liver as compared to the DRH rat liver.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Confusing tumors, especially small tumor nodules, were confirmed by histological examination of slices. in the livers of DRH/Sea and its parental Crj:Donryu rats [9]. Furthermore, comparable numbers of putatively preneoplastic glutathione S-transferase placental form (GST-P)-positive foci were detected after the SoltFarber protocol [7], but the area occupied by GST-P-positive lesions in the liver was much greater in Crj:Donryu rats than in DRH/Sea rats [3].…”
mentioning
confidence: 92%